DaLAJ v.1.0 - Språkbanken Text (University of Gothenburg, 2024)
Dataset for Linguistic Acceptability Judgments (and more), v.1.0., is a collection of sentences from SweLL (Swedish Learner Language) essays. Each DaLAJ sentence contains one error only.

Dataset for Linguistic Acceptability Judgments (and more), v.1.0., is a collection of sentences from SweLL (Swedish Learner Language) essays. Each DaLAJ sentence contains one error only
DaLAJ v.1.0
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik